Letter from Edward N. Kent to James Curtis Booth, October 18, 1854 - Kent, Edward (1854)
Edward N. Kent of the United States Assay Office at New York requests buckskin gloves and other supplies from James Curtis Booth (1810-1888).
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City